2021
DOI: 10.3389/fpsyt.2021.653093
|View full text |Cite
|
Sign up to set email alerts
|

First-Time Users of ADHD Medication Among Children and Adolescents in Germany: An Evaluation of Adherence to Prescribing Guidelines Based on Claims Data

Abstract: Background: Drug utilization studies based on real-world data are vital for the identification of potentially needed improvements to rational prescribing. This is particularly important for the pharmacological treatment of children and adolescents with attention-deficit hyperactivity disorder (ADHD) due to the associated potential side effects and the frequent use. Whereas prevalent use is well-characterized, studies on first-time use of ADHD medication are scarce. This study aimed to evaluate off-label prescr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
(42 reference statements)
1
3
0
1
Order By: Relevance
“…The high off-label use we encountered is in line with the 32% off-label use in children, according to a report from the French Pharmacovigilance Database (Trenque et al 2014) and also in line with Canadian data that indicated that around 25% of ADHD medications were prescribed to school age children for a reason other than ADHD (Brault and Lacourse 2012). In Germany, off-label use of ADHD medication appears considerably lower, accounting for 12.7% of all prescriptions (Scholle et al 2021).…”
Section: Discussionsupporting
confidence: 82%
“…The high off-label use we encountered is in line with the 32% off-label use in children, according to a report from the French Pharmacovigilance Database (Trenque et al 2014) and also in line with Canadian data that indicated that around 25% of ADHD medications were prescribed to school age children for a reason other than ADHD (Brault and Lacourse 2012). In Germany, off-label use of ADHD medication appears considerably lower, accounting for 12.7% of all prescriptions (Scholle et al 2021).…”
Section: Discussionsupporting
confidence: 82%
“…In almost all Asian countries, barring Japan, MPH is the mainstay pharmacological treatment for ADHD. Although the approval status and guidelines recommend MPH and ATX as the first‐line pharmacologic treatment in many European countries, the Canadian ADHD Resource Alliance (CADDRA), and NICE guidelines recommend ATX and GXR as second‐line treatment 4,21,22 . Pharmacological treatment trends in Asian countries and regions may be based on these highly evaluated clinical practice guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Although the approval status and guidelines recommend MPH and ATX as the first‐line pharmacologic treatment in many European countries, the Canadian ADHD Resource Alliance (CADDRA), and NICE guidelines recommend ATX and GXR as second‐line treatment. 4 , 21 , 22 Pharmacological treatment trends in Asian countries and regions may be based on these highly evaluated clinical practice guidelines. The prevalence of ADHD in school‐aged children varies considerably between countries; for example, white individuals have higher rates of ADHD than Asian individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Betrachtet man die wenigen Studien, die störungsspezifisch den Anteil psychotherapeutisch behandelter Kinder und Jugendlicher untersucht haben, zeigt sich diesbezüglich eine große Spannbreite: In einer Untersuchung zur Behandlung der posttraumatischen Belastungsstörung erhielten im Jahr 2017 zwischen 50 % und 78 % aller Kinder und Jugendlichen irgendeine Form von Psychotherapie, hiervon waren etwa 40 % Richtlinientherapie [17]. Eine Studie zur Psychotherapie bei ADHS mit Daten der Jahre 2015-2017 fand hingegen nur einen Anteil von 13 % psychotherapeutisch behandelter Kinder (Anteil von Richtlinienpsychotherapie: 92 %) [26]. In einer Studie zur Therapie von Essstörungen (Anorexie/Bulimie) lag die Psychotherapiequote im Jahr 2009 zwischen 75,7 % und 78,5 % [27] und in einer Studie zur Behandlung depressiver Störungen bei etwa 69 % im Jahr 2009 [28].…”
Section: Originalarbeitunclassified